LANSIA SEHAT DI MASA PANDEMI COVID-19: Lansia Sehat, Aman Terlindungi - Lisdahayati, Lisdahayati; Rohana, I Gusti Ayu Putu Desy; Pome, Gunardi; Folendra Rosa, Eni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The elderly (elderly)in the final stages of the human life cycle. The elderly population in Indonesia is 20.3 million or 10% of the total population. Due to the degenerative process and comorbidities, the elderly group is at risk of dying if infected with COVID-19. The highest mortality due to Covid-19 infection occurred in the elderly group, 44% compared to other age groups. Community service was carried out to socialize techniques for maintaining the health of the elderly during the Covid-19 pandemic to the group of Az-Zainur recitation mothers, Lubuk Batang Baru Village, who are a population at risk for contracting Covid-19. The method used is the didactic method, the counseling is carried out in one direction by the presenter directly to the participants, after delivering the material, then asking questions and conducting demonstrations. The participants of this community service activity were 30 elderly respondents. The result of this community service is the achievement of an increase in elderly knowledge about efforts to maintain the health of the elderly during the Covid-19 pandemic by 60.1%. This community service activity produces posters that are expected to be a reference in educating the elderly to maintain the health of the elderly during the Covid-19 pandemic.